2005
DOI: 10.1007/s10722-005-0225-0
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of genetic diversity in Tunisian durum wheat cultivars and related wild species by SSR and AFLP markers

Abstract: Thirty-four durum wheat cultivars representing the Tunisian durum (Triticum durum Desf.) wheat collection and seven wild species of wheat relatives (Triticum turgidum L., T. dicoccon Schrank., T. dicoccoides (Kö rn) Schweinf., T. araraticum Jakubz., T. monococcum L., Aegilops geniculata Roth, and Aegilops ventricosa Tausch) were analysed with amplified fragment length polymorphism (AFLP) and microsatellite (SSR) markers. Both marker systems used were able to differentiate durum wheat cultivars from the wild re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

16
44
1
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(62 citation statements)
references
References 28 publications
16
44
1
1
Order By: Relevance
“…The locus gwm131 was the most polymorphic, followed by the locus gwm427. Our results are in agreement with the studies of Medini et al (2005) and those of Colomba and Gregorin (2011) conducted on different durum populations and showed the existence of a higher genetic diversity estimated on the base of the use of SSR and AFLP markers. Hamrick and Godt (1997) reported that intra-population genetic diversity of crosspollinated species varies from 10.3% to 26.6%, whereas intra-population genetic diversity of self-pollinated species varies from 0.09% to 0.14%.…”
Section: Discussionsupporting
confidence: 93%
“…The locus gwm131 was the most polymorphic, followed by the locus gwm427. Our results are in agreement with the studies of Medini et al (2005) and those of Colomba and Gregorin (2011) conducted on different durum populations and showed the existence of a higher genetic diversity estimated on the base of the use of SSR and AFLP markers. Hamrick and Godt (1997) reported that intra-population genetic diversity of crosspollinated species varies from 10.3% to 26.6%, whereas intra-population genetic diversity of self-pollinated species varies from 0.09% to 0.14%.…”
Section: Discussionsupporting
confidence: 93%
“…Genetic diversity in different durum wheat germplasm has been estimated using AFLP (Medini et al 2005;Mardi et al 2011), SSR and SSAP (Mardi et al 2011) and AFLP markers (Maccaferri et al 2007), but studies on the genetic diversity of Iranian landrace durum wheat are limited. The largest variability for yield and yield-related traits was recorded in Iranian durum wheat landraces, which is in agreement with its proximity to the Fertile Crescent, the origin for domestication of wheat (Harlan 1986;Fayaz et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, microsatellites exhibit a codominant inheritance (Hernández et al 2002), which is essential for effective discrimination between closely related lines (Akkaya et al 1992). Microsatellite markers are currently used to identify genotypes, quantitative trait loci (QTLs) and genetic diversity (Leišová & Ovesná 2001;Medini et al 2005;Roussel et al 2005).…”
mentioning
confidence: 99%